Clinical Spectrum of COVID-19 Patients after Vaccination - Asif Niaz; Muhammad Tahir Younas; Shaista Nayyar; Sabeeha Yousaf; Zainab Rizwan; Ainan Arshad (Pakistan Armed Forces Medical Journal, 2022)
Objective: To examine the clinical severity and magnitude of COVID-19 patients after the second dose of the COVID-19 vaccine.